2015
DOI: 10.1093/annonc/mdu549
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile determined by data-mining analysis set into clusters of non-small-cell lung cancer patients according to prognosis

Abstract: Our results provide evidence that complex cytokine networks may be used to identify patient subgroups with different prognoses in advanced NSCLC. These cytokines may represent potential biomarkers, particularly in the immunotherapy era in cancer research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 25 publications
1
58
2
1
Order By: Relevance
“…Clustering analyses of pretreatment serum CAFs to classify patients into subgroups have been reported in renal cell carcinoma and non-small cell lung cancer [16,19], and several studies showed that a distinct CAF profile could predict clinical outcomes [15][16][17][18][19]. However, although associations between inflammatory cascades or angiogenic factors, such as VEGF, and clinical outcomes have been reported in GC [24], comprehensive Signature of cytokines and angiogenic factors (CAFs) defines a clinically distinct subgroup… 167 explorations of circulating factors and the relationships with clinical outcomes have not been published for GC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clustering analyses of pretreatment serum CAFs to classify patients into subgroups have been reported in renal cell carcinoma and non-small cell lung cancer [16,19], and several studies showed that a distinct CAF profile could predict clinical outcomes [15][16][17][18][19]. However, although associations between inflammatory cascades or angiogenic factors, such as VEGF, and clinical outcomes have been reported in GC [24], comprehensive Signature of cytokines and angiogenic factors (CAFs) defines a clinically distinct subgroup… 167 explorations of circulating factors and the relationships with clinical outcomes have not been published for GC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of CAFs have indicated that an understanding of the delicate networking of CAFs is necessary to correlate CAF levels to clinical outcomes, because the biological activity of circulating factors might be the result of the interactions of CAFs rather than the action of single CAFs [15][16][17][18][19]. A previous study in renal cell carcinoma identified 6 CAFs as significant predictive factors for the selection of a combination regimen of sorafenib and interferon-alpha compared to sorafenib alone [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these studies found out that the serum IL-29 levels were higher in the control group than those in the non-small cell lung cancer (NSCLC) patients, but there was no statistically significant difference [34,35]. We found that the difference between baseline serum IL-29 concentrations between GC patients and healthy controls was not statistically significant (p= 0.627), and furthermore, we concluded that patients without metastasis had higher serum IL-29 concentrations than the patients with metastasis (p=0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of IL-33 have been reported to be reduced in the plasma of non-small cell lung cancer patients relative to controls [105], and levels of IL-33 have also been shown to negatively correlate with tumour stage in multiple myeloma patients [106]. Interestingly, IL-33 has been observed to be increased in response to viral infection and to be important for the eradication of a viral insult, as it can differentiate CTLs into anti-viral CD8 + T cells [107].…”
Section: "Wounds That Do Not Heal" -Understanding the Role Of Il-33 Imentioning
confidence: 99%